2018
DOI: 10.1002/rmb2.12250
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study and case reports on endometrial microbiota and pregnancy outcome: An analysis using 16S rRNA gene sequencing among IVF patients, and trial therapeutic intervention for dysbiotic endometrium

Abstract: PurposeThe present study aimed to analyze the pregnancy outcomes of IVF patients presenting Lactobacillus‐dominated microbiota (LDM) or non‐Lactobacillus‐dominated microbiota (NLDM) of their endometrium and to report cases who were treated for NLDM concurrently with antibiotics and prebiotic/probiotic supplements in a Japanese infertile population.MethodsNinety‐two IVF patients were recruited from August 2017 to March 2018. Endometrial fluid samples for sequencing were collected using an IUI catheter. The bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
105
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 16 publications
2
105
0
4
Order By: Relevance
“…Atopobium [6,[8][9][10], Bacteroides [12], Betaproteobacteria [12], Bifidobacterium [5,[8][9][10][11]13,104], Burkholderia [7], Chitinophagaceae [12], Corynebacterium [104], Escherichia/Shigella [10,12], Flavobacterium [4], Gardnerella [5][6][7][8][9][10][11]13], Lactobacillus [4][5][6][7][8][9][10][11]13,104], Megasphaera [9,10], Pelomonas [12], Prevotella [8][9][10][11]13], Pseudoalteromonas [5], Rhodanobacter [5], Sneathia [8,9], Staphylococcus [8]…”
Section: Healthymentioning
confidence: 99%
See 1 more Smart Citation
“…Atopobium [6,[8][9][10], Bacteroides [12], Betaproteobacteria [12], Bifidobacterium [5,[8][9][10][11]13,104], Burkholderia [7], Chitinophagaceae [12], Corynebacterium [104], Escherichia/Shigella [10,12], Flavobacterium [4], Gardnerella [5][6][7][8][9][10][11]13], Lactobacillus [4][5][6][7][8][9][10][11]13,104], Megasphaera [9,10], Pelomonas [12], Prevotella [8][9][10][11]13], Pseudoalteromonas [5], Rhodanobacter [5], Sneathia [8,9], Staphylococcus [8]…”
Section: Healthymentioning
confidence: 99%
“…The initial studies of endometrial microbiome suggest its association with reproductive outcomes in assisted reproduction [4][5][6][7][8][9][10][11][12][13] and with different gynaecological pathologies such as chronic endometritis (CE) [14][15][16], endometriosis [13,[17][18][19][20][21], dysfunctional endometrial bleeding [22], endometrial polyps [16], and endometrial cancer or hyperplasia [23][24][25]. Nevertheless, causality has been difficult to prove because the reproductive tract represents a polymicrobial niche [26], and it is not clear whether dysbiosis within the uterus is a cause or a consequence of a pathology.…”
Section: Introductionmentioning
confidence: 99%
“…When we analyzed the taxonomic characterization, we also implantation (18). In this preliminary study, the predominance of Lactobacillus was favorable in terms of the pregnancy rate; however, the results were not as significant as in the previous pilot study (17); the reasons for this may be due to the limited number of cases, short follow-up period, or ethnic differences. In an other study also concluded that women with an abnormal vaginal microbiota are approximately 1.4 times less likely to become pregnant after in vitro fertilization treatment, compared to women with a normal microbiota pattern (19).…”
Section: Discussionmentioning
confidence: 87%
“…The ability of lactobacilli to inhibit infection without inducing inflammation can maximize fertility and favour pregnancy outcomes(16). The presence of a non-Lactobacillus-dominated microbiome (NLDM) is associated with a lower rate of implantation, pregnancy rate, pregnancy progression and live birth(17). Moreno et al reported that a relative abundance of lactobacilli of less than 90% in endometrial fluid was predictive of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation